TiO2-based MIM capacitors featuring suppressed leakage current by embedding Ge nanocrystals. Issue 18 (5th March 2015) - Yu, Meng-Ting; Chen, Kuen-Yi; Chen, Yu-Hsun; Lin, Chia-Chun; Wu, Yung-Hsien
<x xml:space="preserve">Abstract</x> Leakage current suppression of TiO2-based MIM capacitors is achieved by using plasma treatment and embedding Ge nanocrystals.